PENGARUH PENGETAHUAN PAJAK, KESADARAN PAJAK, DAN PENDAPATAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK MEMBAYAR PAJAK BUMI DAN BANGUNAN DI KELURAHAN RANDUSARI: (STUDI KASUS WILAYAH RW 1) - Endah Kurnia Hastuti; Wikan Budi Utami; Desy Nur Pratiwi (Jurnal Ilmiah Manajemen dan Akuntansi, 2024)
The study aims to analyze the impact of tax knowledge, tax awareness and taxable income on compliance with taxable payers of land and buildings in Kelurahan Randusari region RW 1. The sample of 88 respondents was taken with the Slovin formula. The variables used include tax knowledge (X1), tax awareness (X2), taxable income (X3) and taxable compliance (Y). The data analysis used in this study uses descriptive analysis, validity test, feasibility test, and classic assumption test, with hypothesis testing using double linear regression analysis, test f, test t and determination coefficient. The results of the research carried out are tax knowledge (X1) and tax awareness (X2) have a significant impact on tax compliance, while taxable income (X3) has no significant effect on taxable compliance (Y).